VD_FINDINFO Jug / 2020 / 37 vom 27. August 2019 - VD Tribunal cantonal (2019)
MISE EN DANGER DE LA VIE D'AUTRUIART. 129 CP, DISPOSITIONS PÉNALES DE LA LCR | 106 CP, 46 al. 1 CP, 47 CP, 49 al. 1 CP, 50 CP, 66a CP, 90 ch. 2 LCR, 92 al. 1 LCR